Al-Ihtibāk ‘Inda Al-Tafsīr Ibni ‘Asyūr Min Khilāli Sūraħ Al-Baqaraħ Ilā Sūrati Al-A‘Rāf : الاحتباك عند الطاهر ابن عاشور من خلال صورة البقرة إلئ الأعراف - Hadi, Lalu Nuzul Ilham; Tarmom, Nabil Ahmed; Suparman, Yogi; Safei, Abdullah; Nurzen, Kopri (Civilization Research: Journal of Islamic Studies, 2022)
This Research, talks about the places of Al-Ihtibâk’s Rhetoric which Al- ṭāhir Ibn ‘Asyūr referred to in his Tafsîr (interpretation). In Writing His research, The researcher followed the Descriptive Qualitative Approach with Literature Study Method. The researcher has reached: (1). The samples of Al-Ihtibâk’s Rhetoric from Surat Al-Baqarah to Surat Al- A’raf that the researcher may have reached: were nine places; three places in Surat Al-Baqarah, Five places in Surat Al-An’am, and one place in Surat Al-A’raf. (2). Only Al- ṭāhir Ibn ‘Asyūr explained and stated or declarated Al-Ihtibâk’s Rhetoric in the following places: Two places of Surat Al-Baqarah, wich are in verse – 228 and verse – 251. And in four places of Surat Al-An’am; which are in verse ( 9, 17, 28, 71-72). (3). Al-Ihtibâk’s Rhetoric in The interpretation of Ibn ‘Ashour was strengthened by the following interpreters such as: Al-Thabarî ( d. 310 AH),  and Al-Wâhidî (d.468 AH), and Al-Zamakhsharî (d.538 AH), and Ibn ‘Athiyah ( d. 542 AH), and Ibn Al-Jauzî ( d. 597 AH), and Fakhruddîn Al-Râzî ( d. 606 AH), and Al-Qurthubî ( d.671 AH), and Al-Nasafî ( d. 710 AH), and Abu Hayyân ( d. 745 AH), and Al-Biqâ’î ( d. 885 AH). (4). Al-Thabarî and Al-Zamakhsharî.